Релаксаційна модель механічної поведінки пісковика при квазістатичному навантаженні - Вахненко, В.О.; Вахненко, О.О.; Даниленко, В.А. (Видавничий дім "Академперіодика" НАН України, 2007)
We suggested, based on the relaxation approach, a phenomenological model to describe the stress-strain properties of the Berea sandstone under slow loading. The model allows one to recover qualitatively, as well as in some cases quantitatively, the main experimental observations, in particular, the hysteretic loops in stress-strain curves. Modeling the stress-strain dependences reproduces, in essence, the sandstone state equation.